The Penetration Capacity of a 20 x 102 mm Frangible Armor Piercing Projectile - Badea, Mihaela; Zisopol, Dragos Gabriel; Hadar, Anton; Nastasescu, Vasile (Engineering, Technology & Applied Science Research, 2025)
The aim of this work was to evaluate the penetration capacity of armor plates by the 20x102 Frangible Armor Piercing (FAP) projectile. The projectile was numerically modeled using four different variants, each designed to simplify the calculations and avoid the spread of classified information. These variants included the external geometric shape, external dimensions, mass, and impact speed. Deploying the novelty concept of the equivalent bullet (one that preserves the parameters that determine the depth of penetration), this research utilized four different bullet designs. These models were quantitatively evaluated and validated by comparing the numerically predicted penetration performance with the experimental testing results. The results led to errors just below 1%, except Model-4 which exceeded 30%. This work is useful not only to researchers in the field of terminal ballistics, but also in a general filed of researchers engaged in Finite Element Method (FEM).